Overview of research on traditional medicinal ingredients and raw materials mentioned in the source texts of Ami barigch-5 powder medicine - Bold, Myagmarsuren; Unenbat, Bat-Oyun; Boldsaihan, Munkhzaya; Ganbold, Enkhbold; Tumenbat, Tsetsegdari; Sharavyn, Bold; Luvsan, Khurelbaatar; Battsengel, Odonchimeg; Ryenchindorj, Lkhaasuren (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
Based on the results of recent scientific research, Mongolian traditional medicine is one of the ancient medical practices with a history spanning 5,000 years. An invaluable contribution to the development of formulations in Mongolian traditional medicine is the work by Choijamts, titled “The Heart Essence of the Elixir Compiled from Various Essential Texts of Medicine: Ngo mtshar dga ston gter mdzod”. This work became widely renowned for its detailed explanation of the laws governing human health, the causes of illness, and the methods of healing, as well as for its exceptional collection of medicinal recipes. With the increasing need to systematically study traditional and modernized uses of medicines derived from plants, animals, and minerals, it is essential to elevate research to a new level. By studying traditional technologies and identifying proven medicinal compounds from ancient and rare texts, this research focuses on exploring the formula of Srog dzin-5 found in Choijamts’s work. This approach was chosen to contribute to the scientific understanding and application of traditional medicine. The Buddhist Lama Choijamts lived between 1860 and 1928. His work, “The Heart Essence of the Elixir Compiled from Various Essential Texts of Medicine: Ngo mtshar dga ston gter mdzod” commonly referred to as “Ngo mtshar dga ston gter mdzod” was initiated in 1921 and meticulously revised and completed in 1922. This monumental text comprises 129 chapters. The 58th chapter specifically addresses remedies for heart diseases, prescribing the “Ami Barigch-5” formula mixed with molasses. It describes the medicine as effective for treating heart conditions, insanity, seizures, emotional distress, heart palpitations, and shortness of breath. The composition and potency of this powdered medicine were examined in comparison to other formulations and raw materials described in historical texts and primary sources. Research further indicates that the Ami Barigch-5 powder medicine, with its carefully curated ingredients and therapeutic properties, has been validated through pharmacological and clinical trials, confirming its efficacy as a traditional medicinal recipe.